Clinical effect of enteral nutrition support during neoadjuvant chemotherapy on the preservation of skeletal muscle mass in patients with esophageal cancer. Issue 6 (June 2021) - Kita, Ryosuke; Miyata, Hiroshi; Sugimura, Keijiro; Tanaka, Koji; Makino, Tomoki; Yamashita, Kotaro; Yamasaki, Makoto; Motoori, Masaaki; Shiraishi, Osamu; Kimura, Yutaka; Yasuda, Takushi; Yano, Masahiko; et al.
Summary: Background & aims: Reductions in skeletal muscle mass during neoadjuvant therapy can have a negative effect on short- and long-term outcomes in patients with esophageal cancer. However, effective treatment for suppressing reductions in skeletal muscle mass during neoadjuvant therapy has not been established. Methods: Eighty-seven patients were included in this study who were enrolled in a previous randomized study comparing the effects of enteral nutrition (EN) and parenteral nutrition (PN) on chemotherapy-related toxicities during neoadjuvant chemotherapy in esophageal cancer patients. Changes in skeletal muscle mass during neoadjuvant therapy were compared between the two groups. Results: Skeletal muscle mass index (SMI) decreased from 45.8 cm 2 /m 2 before treatment to 43.7 cm 2 /m 2 after neoadjuvant chemotherapy in 87 patients (p = 0.092). The total calorie intake during neoadjuvant therapy was equal between the two groups. SMI reduction was significantly smaller in the EN group than in the PN group (−1.4 cm 2 /m 2 vs −3.0 cm 2 /m (Gebski et al., 2007) [2], p < 0.001). EN support was identified as the only independent factor adversely associated with severe SMI reduction (p < 0.001). Patients with low SMI after neoadjuvant chemotherapy were more susceptible to postoperative complications than patients with moderate SMI (47.6% vs 16.7%, p = 0.007), especially pulmonary complications (31.8% vs 10.8%, p = 0.003). Patients with low SMI after neoadjuvant chemotherapy tended to show worse prognosis than patients with moderate SMI (5-year overall survival rate: 43.8% vs 62.1%, p = 0.194). Conclusions: Compared with PN support, EN support during neoadjuvant chemotherapy suppressed reductions in skeletal muscle mass in patients with esophageal cancer. Highlights: Enteral or parenteral nutrition was performed during neoadjuvant chemotherapy. Enteral nutrition suppressed skeletal muscle loss in esophageal cancer patients. Skeletal muscle loss during therapy negatively affected outcome in cancer patients.